Representations of forced displacement in Colombian fiction cinema: years 2003 to 2011 - Uribe Montes, Jhon Alexander (Escribanía, 2018)
The following exhibition of results is the product of a research project thatasks about the way in which the arts rewrite and interpret Colombian history.Specifically, how the Colombian fiction cinema between the years 2003 to2011 gave account of those multiple realities product of the war. Today, witha peace process signed with the FARC guerrillas and the maximum challengeof an implementation that guarantees real peace, it is pertinent to examinehistory, build memory processes and draw attention to the strategies used toreveal these realities.